The Correlation Between Knowledge and Exclusive Breastfeeding Behavior Among Kindergarten Teachers - Ghina Fatima Salsabila; Wiwin Mintarsih; Nita Nurvita (Poltekkes Kemenkes Semarang, 2020)
Background: The low coverage of exclusive breastfeeding could had an impact on the quality of life for the nation's future generations and also on the national economy. The level of education of the mother can be a cause of the low level of exclusive breastfeeding, most mothers were less aware of the importance of breast milk as the baby's main food. Breastfeeding behavior was related to lack of knowledge, beliefs or perceptions and wrong attitudes from mothers regarding breast milk. The purpose of this study was to describe the relationship between knowledge and exclusive breastfeeding behavior in kindergarten teachersMethods: This study was descriptive analytic study with the cross sectional approach. The population was all female kindergarten teachers in Tawang District who had 0-2 years of children, as many as 48 people, using a total sampling technique.Results: Bivariate analysis was performed used the Spearman rank test. Based on the results it was found that the significance level of p value was 0.000Conclusion: It meant that there was a correlation between knowledge and the behavior of exclusive breastfeeding in kindergarten teachers.